Agroforestry untuk agribisnis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Agroforestry, a system of land management which combines the protective (and also productive) characteristics of forestry with the productive attributes of agriculture, is considered to be suitable for ecologically fragile areas while at the same time it may also provide strong ground for developing rural-agroindustry. Agroforestry ventures could be carried out either on agricultural or on forest lands. Outside the forest there is enormous potential for introducing trees on farm lands that are conventionally strictly agricultural. Under a modified management practices, forest lands could also be used for a greater food production base for rural population. Agribusiness activities which link the sources of material directly with the processing industry is a logical alternative to answer the long standing problem being faced by farmers, i.e. providing secure market for their farm products. To the forest managers being occupied with security problem, this approach will be relaxing pressures on their forest, helping farmers to improve their welfare, contributing to the implementation of the national food security program, while expanding the export of commodities other than oil and gas.